TRACE LEVEL DETERMINATION OF SODIUM CHLORIDE AND SODIUM SULFATE CONTENT IN SODIUM LAURETH SULFATE RAW MATERIAL USING COUNTER CATION-EXCHANGE HPLC WITH INDIRECT ULTRAVIOLET DETECTION - RAO KATAKAM, LAKSHMI NARASIMHA; DONGALA, THIRUPATHI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: A novel study on a new liquid chromatographic approach has been developed and validated for simultaneous determination of trace level determination of sodium chloride and sodium sulfate measures its impurities using counter cation-exchange high-performance liquid chromatography with indirect ultraviolet (UV) detection. Methods: Chromatographic separation is developed and validated on a Hamilton PRP-X100 column with a mobile phase contained a mixture of the para-hydroxybenzoic acid buffer with a pH of 9.0 and methanol. Chromatography is developed at a flow rate of 2.0 mL/min with an indirect UV determination at 310 nm at a sensitivity level of 0.5%. The optimized method was validated as per the ICH Q2 guidelines. Results: The retention times of chloride and sulfate were about 2.8 and 7.6 min, respectively. The resolution between chloride and sulfate peaks is >4. Regression analysis confers a correlation coefficient for the stated compounds that are found to be >0.999. Conclusion: A novel analytical method was validated as per the ICH method validation guidelines and found to be selective. Hence, the validated analytical method was precise, specific, and accurate, and it is more economic and simple for the determination of inorganic impurities.